The Relationship Between Service Quality and Patients' Revisit Interest at Beutong Public Health Centre, Beutong Subdistrict, Nagan Raya District - Susanti, Lia; Hasnur, Hanifah; Akbar, Fahrisal (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: The significant decline in the number of patient visits at Beutong Public Health Centre, Beutong Subdistrict, Nagan Raya District, which reached 73% between 2021 and 2022, serves as a critical backdrop for this study. This research aims to analyse the factors influencing healthcare service quality and patients' revisit interest by focusing on five key service dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The study is descriptive-analytical and was conducted at the Beutong Public Health Centre from March to April 2024. The sample consisted of 100 respondents selected using purposive sampling based on inclusion criteria. Data were collected through questionnaires and secondary data from the health centre and analysed using SPSS version 24. The results showed that all five dimensions of healthcare service—reliability, responsiveness, assurance, empathy, and tangibles—influence patients' revisit interest. Specifically, the assurance variable had the most significant impact, with 77% of respondents indicating positive revisit interest. Reliability influenced 69% of respondents, empathy 68%, tangibles 63%, and responsiveness 53%. However, statistical analysis revealed that only assurance had a statistically significant effect (p 0.05), while reliability, responsiveness, empathy, and tangibles did not show significant influence (p 0.05). Based on these findings, it is recommended that Beutong Public Health Centre improve healthcare service quality by focusing on enhancing staff reliability through regular training, strengthening responsive communication channels to address patient complaints, improving staff credibility and professionalism through certification and continuous training, and upgrading the physical facilities of the health centre.